1998
DOI: 10.1097/00004872-199816121-00021
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous nitric oxide in the nucleus tratus solitarii on baroreflex control of heart rate in spontaneously hypertensive rats

Abstract: NO modulates, at the NTS level, the baroreceptor reflex control of HR in both SHR and WKY not by altering the gain, but by increasing HR range during afferent stimulation. In SHR the depressed NO modulation is in accordance with the smaller NOS activity in the dorsal brain stem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 22 publications
7
42
1
2
Order By: Relevance
“…For instance, using in vivo unanesthetised decerebrate rats, elegant work from Paton's laboratory has shown that NO is able to act in the caudal NTS to attenuate the gain of the vagal component of the cardiac baroreflex (24,25). This is consistent with other in vivo evidence, which has shown that administration of NOS inhibitors in the NTS increased baroreflex sensitivity in both anesthetized and conscious animals (26,27). Conversely, Chowdhary and Townend (28) have reported that NO serves to inhibit central sympathetic outflow and studies by Di Paola et al (29) show that the neurotransmitter L-glutamate which promotes the release of NO from nitrergic neurones stimulates, rather than inhibits, baroreflex processing within the NTS.…”
Section: Discussionsupporting
confidence: 73%
“…For instance, using in vivo unanesthetised decerebrate rats, elegant work from Paton's laboratory has shown that NO is able to act in the caudal NTS to attenuate the gain of the vagal component of the cardiac baroreflex (24,25). This is consistent with other in vivo evidence, which has shown that administration of NOS inhibitors in the NTS increased baroreflex sensitivity in both anesthetized and conscious animals (26,27). Conversely, Chowdhary and Townend (28) have reported that NO serves to inhibit central sympathetic outflow and studies by Di Paola et al (29) show that the neurotransmitter L-glutamate which promotes the release of NO from nitrergic neurones stimulates, rather than inhibits, baroreflex processing within the NTS.…”
Section: Discussionsupporting
confidence: 73%
“…2 NO-mediated actions in the CNS include central vascular regulation 27 and the baroreflex control of HR. 18 Antihypertensive activity, based on the facilitated release of GABA and glutamate in the CNS, and NO production are suggested to result in diminished transmission of sympathetic tone to the periphery. 27 However, no Bj-PRO-10c-induced changes of the sympathetic renal activity of SHRs were observed under anesthesia, and MAP of these animals also remained unchanged (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…17 Changes in neural-cardiovascular integration due to NO deficiency may be the main cause of autonomic abnormalities in several models of experimental hypertension 2 as a consequence of impaired arterial baroreflex. 3,18 As a result of augmented ASS activity, an enzyme also expressed in the CNS, 6 and central effects on the control of blood pressure 11,14 in the presence of Bj-PRO-10c, we expected to observe increased NO production in the brain and improved arterial baroreflex function in conscious SHRs. Therefore, this study was designed to examine the effects of Bj-PRO-10c on baroreflex sensitivity in SHRs and to elucidate involved mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the dose-response curve was not linear when high concentrations of arginine were used in NOS assay. Thus, the working solution with the best specific activity was obtained in the presence of 120 nM of L-arginine with a fixed concentration of The dependence of the presence of co-substrate and cofactors in NOS activity have been reported in different tissue preparation, such as kidney, myenteric plexus, dorsal brain stem, neutrophils, dorsal periaquedutal gray, spinal cord and LLC-PK 1 cells (Lincoln, Messersmith, 1995;Mckee et al, 1994;Barjavel, Bhargava, 1995;Pontieri et al, 1998;Cerchiaro et al, 2001;Chiavegatto et al, 1998). Our results also demonstrated a dependence of the presence of co-factor when measuring NOS activity in platelet homogenate.…”
Section: Discussionmentioning
confidence: 99%